Analisis Efektivitas Strategi Manajemen Keuangan dalam Mengendalikan Arus Kas dan Modal Kerja - Firman Waruwu; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyze the effectiveness of financial management strategies in controlling cash flow and working capital at Kurnia Karangjati Supermarket. The problem focuses on how financial management strategies are implemented in daily operational practices and the extent to which these strategies support operational continuity and financial stability in a local retail business. To approach this issue, theories of financial management, cash flow management, and working capital management are employed. Data were collected through in-depth interviews, direct observation, and documentation involving parties responsible for financial and operational management, and were analyzed using a qualitative descriptive approach. The findings indicate that the financial management strategies applied are relatively simple and oriented toward short-term operational needs, relying on daily cash monitoring, routine recording of cash inflows and outflows, operational cost control, and gradual inventory management. These strategies are effective in maintaining daily cash availability and working capital flexibility; however, they are not yet supported by formal budgeting and systematic cash flow analysis. This study concludes that strengthening financial planning and periodic evaluation is essential to improve the sustainability and effectiveness of financial management in local retail businesses.